Pengaruh Struktur Modal, Likuiditas, dan Profitabilitas terhadap Nilai Perusahaan Properti Real Estate di Bursa Efek Indonesia tahun 2022-2024 - Rifa Jati Apriasti; Sanya Aurelia; Alvin Renata Maulana; Ad Tyo Ramdhanu; Riska Fii Ahsani (JURNAL EKONOMI PERJUANGAN, 2026)
This paper aims to investigate the correlation between capital structure, liquidity, and profitability and their effect on firm value in the property and real estate industry listed on the Indonesia Stock Exchange for the years 2022 to 2024. Firm value reflects investors perceptions of a company's performance and prospects, thus becoming an important indicator in improving shareholder welfare. The data used are secondary data obtained from the company's financial statements. Data analysis was performed using multiple linear regression methods with statistical software, as well as through classical hypothesis testing and hypothesis testing at a 5% significance level. The independent variables in this study consist of capital structure, represented by the debt-to-asset ratio (DAR), liquidity, measured by the current ratio (CR), and profitability, proxied by return on assets (ROA). Firm value serves as the dependent variable, assessed using Tobin’s Q. The findings indicate that, individually, capital structure tends to exert a negative influence on firm value, whereas profitability demonstrates a significant positive impact. Liquidity shows varying effects on firm value. Simultaneously, all three variables have a significant effect on firm value. The findings of this study are anticipated to provide valuable input for corporate management in formulating financial strategies and for investors in making informed investment decisions.